The Impact of Social Media Influencer Attributes on Brand Trust and Sporting goods Purchase Intention and the Role of Gender: An Empirical Research on China - Yu, Tao (2022)
As social media has become an indispensable entertainment in people’s daily lives, influencers have emerged in various fields. Companies are finding that using influencer marketing can be an effective way to promote their brands and products. However, current research on influencer marketing is based on the cosmetics or fashion industries, with little research on the sporting goods industry. It is also worth noting that the Chinese social media market is different from the international one due to the limitations of the Chinese internet. There is a need to study how the sporting goods industry in China is driven by influencer marketing. In addition, previous studies have paid little attention to whether gender-differentiated followers generate different purchase intentions. This study will fill the above research gaps. The purpose of this research is to explore the impact of influencer attributes on brand trust and sporting goods purchase intention in China’s social media market and the role of gender differences. This study adopts the quantitative research method. Through random sampling, 238 valid questionnaires are collected, and SPSS 28 is used to analyse the data and verify hypotheses. The findings reveal that influencer attributes positively affect brand trust, which in turn positively affect sporting goods purchase intention. Brand trust plays a mediating role in the above relationship. The influencer’s expertise is the attribute that has the greatest impact on followers’ intention to purchase sporting goods. Furthermore, no moderating effect of gender is found between influencer attributes and sporting goods purchase intention. The key contribution of this research is to add new content to the literature of influencer marketing and the sporting goods industry and provide a conceptual framework related to influencer attributes, brand trust, and purchase intention. Scholars can use this framework to further expand in the new context of influence marketing. Meanwhile, the managerial contribution of this research is to provide practical recommendations for marketers and influencers on how to implement influencer marketing better.